Histology of hemangioblastoma treated with stereotactic radiosurgery confirms its effectiveness. (May 2018) - Nambu, Shohei; Otani, Ryohei; Higuchi, Fumi; Uzuka, Takeo; Matsuda, Hadzki; Kim, Phyo; Ueki, Keisuke
Graphical abstract: Highlights: Stereotactic radiosurgery with 20 Gy eliminated all stromal cells of hemangioblastoma. Few report evaluated histology of hemangioblastoma after stereotactic radiosurgery. The damaged remnant vessels lacking endothelial cells were also observed. Leakage from the damaged vessels may be a cause of cyst enlargement. Abstract: Hemangioblastoma is usually amenable to total surgical resection, but indication for surgery can be hampered by its location, multiplicity, or repeated recurrences frequently observed in patients with von Hippel Lindau disease (VHLD). Stereotactic radiosurgery (SRS) has been administered for such cases as an alternative therapeutic option with generally favorable clinical response, but the effect of SRS has not been underscored by histological examination of the treated hemangioblastoma. Here we present histology of VHLD-associated hemangioblastoma tissue resected three months after SRS because of cyst enlargement. It confirmed that hemangioblastoma cells totally disappeared after SRS with a marginal dose of 20 Gy. Furthermore, Electron microscope revealed that endothelial cells of the vascular structure disappeared while maintaining the basement membranes, and leakage of intraluminal contents was observed around the structure. We showed the SRS was effective for hemangioblastoma pathologically at least with the marginal dose of 20 Gy. Leakage of intraluminal contents from the damaged vascular structure losing the endothelial cells is one possible mechanism for the cyst enlargement, and it may be a reason of poor control rate of SRS for the cystic hemangioblastoma.